Answers to Questions on Teaching Technology. Revised Edition - International Technology Education Association, Reston, VA.; Maley, Donald; International Technology Education Association, Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This publication for technology teachers is developed around a series of questions commonly raised about the integrated approach to teaching technology. Responses have been provided by eight experienced teachers. An introduction explains the integrated approach and provides a schematic drawing showing the principal phases of the program plus the inputs to each phase. The first series of questions is related to advance preparation. Questions address resource materials, type of classes, getting started, advance preparations, class size, at-risk students, implementation strategies, teaching materials, and costs. Questions on introducing the integrated approach cover the first weeks, student and parent acceptance, and public relations. A series of questions on student research addresses helping students, getting results, writing and checking letters, library research, reluctant students, and integration of math and science. Questions regarding construction activities discuss class control, ensuring student success, time devoted to construction, students who finish early, and students who do not finish. Other questions focus on the seminar (the purpose, preparing students, and the teacher's role) and evaluation of students. The final section answers questions on getting more help, quick start techniques, suggestions for supervisors and administrators, instructional formats, and organization. (YLB)
Availability: International Technology Education Association, 1914 Association Drive, Reston, VA 22091 ($8.50; $7.50, members).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Techniques; Elementary Secondary Education; Industrial Arts; Integrated Activities; Postsecondary Education; Program Implementation; Seminars; Student Evaluation; Student Research; Teaching Methods; Technology; Information Analyses